Effects of whole-body vibration on reproductive physiology in a rat model of whole-body vibration. Issue 23 (2nd December 2022) - Krajnak, K.; Waugh, S.; Welcome, D.; Xu, X.S.; Warren, C.; McKinney, W.; Dong, R.G.
ABSTRACT: Findings from epidemiological studies suggest that occupational exposure to whole-body vibration (WBV) may increase the risk of miscarriage and contribute to a reduction in fertility rates in both men and women. However, workers exposed to WBV may also be exposed to other risk factors that contribute to reproductive dysfunction. The goal of this experiment was to examine the effects of WBV on reproductive physiology in a rat model. Male and female rats were exposed to WBV at the resonant frequency of the torso (31.5 Hz, 0.3 g amplitude) for 4 hr/day for 10 days. WBV exposure resulted in a significant reduction in number of developing follicles, and decrease in circulating estradiol concentrations, ovarian luteinizing hormone receptor protein levels, and marked changes in transcript levels for several factors involved in follicular development, cell cycle, and steroidogenesis. In males, WBV resulted in a significant reduction in spermatids and circulating prolactin levels, elevation in number of males having higher circulating testosterone concentrations, and marked alterations in levels of transcripts associated with oxidative stress, inflammation, and factors involved in regulating the cell cycle. Based upon these findings data indicate that occupational exposure to WBV contributes to adverse alterations in reproductive physiology in both genders that may lead to reduction in fertility.